Later onset of Childhood Disintegrative Disorder (CDD): a case report. Issue 4 (4th July 2022) - Di Vara, Silvia; Guerrera, Silvia; Valeri, Giovanni; Vicari, Stefano
ABSTRACT: Childhood Disintegrative Disorder (CDD) is a rare condition characterized by regression of developmental and behavioral functioning after a period of apparently normal development, with an age of onset around 4 years. CDD is not included within the latest edition of the Diagnostic and Statistical Manual of Mental Disorders. We present a case report of an 11-year-old male who achieved normal development for up to 7 years followed by a deterioration of previously acquired linguistic, intellectual, and social skills. Following treatment with lithium carbonate combined with risperidone, the patient experienced a reduction in irritability and aggression. CDD is a rare condition; therefore, the data presented may be useful to investigate its characteristics of the onset, to improve the understanding of the aspects of differentiation from the Autism Spectrum Disorder and finally to propose the possibility of treatment